2021
DOI: 10.3390/biochem1020008
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Antibodies Directed against the α-Gal Epitope

Abstract: The α-Gal epitope is an immunogen trisaccharide structure consisting of N-acetylglucosamine (GlcNAc)β1,4-galactose (Gal)α1,3-Gal. It is presented as part of complex-type glycans on glycoproteins or glycolipids on cell surfaces of non-primate mammalians. About 1% of all antibodies in human sera are specific toward α1,3-Gal and are therefore named as anti-α-Gal antibodies. This work comprises the purification and characterization of anti-α-Gal antibodies from human immunoglobulin G (IgG). A synthetically manufac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Galili et al (1984) established that the level of anti-α-Gal Abs in healthy donors was 1% [8]; Yu et al (1996) quantified by ELISA that the value was in the range of 0 to 15 µg/mL [27], and Tomlinson and Nussenzweig (1997) established this value between 0.25 and 0.5% of total Igs [48]; Obukhova et al (2007) indicated that the level of Igs against α-Gal in healthy donors was about 10-fold less than the established by Galili et al (1984) [49]. Recently, Zappe et al (2021) published that the level of IgG anti-α-Gal in a commercial concentrate of human IgG is about 10% (IgG1 isotype) [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galili et al (1984) established that the level of anti-α-Gal Abs in healthy donors was 1% [8]; Yu et al (1996) quantified by ELISA that the value was in the range of 0 to 15 µg/mL [27], and Tomlinson and Nussenzweig (1997) established this value between 0.25 and 0.5% of total Igs [48]; Obukhova et al (2007) indicated that the level of Igs against α-Gal in healthy donors was about 10-fold less than the established by Galili et al (1984) [49]. Recently, Zappe et al (2021) published that the level of IgG anti-α-Gal in a commercial concentrate of human IgG is about 10% (IgG1 isotype) [50].…”
Section: Discussionmentioning
confidence: 99%
“…There are several works on the Ab titers of the different Ig isotypes and IgG subclasses expressed in both AGS patients and healthy donors, including their relationship to the blood group of the individuals [46,47] and, the published data on the concentration of IgG to α-Gal in normal human serum are controversial depending on the methodology used for quantification. [37,[48][49][50] The objective of our study was to quantify, by means of an automated and standardized method, the levels of sIgG to α-Gal in four different groups of adult subjects: clinical diagnosed AGS-patients, atopic subjects, healthy donors, and in a group of subjects bitten by ticks but who had not developed AGS. The aim was to stablish a sIgG to α-Gal cut-off value.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-Gal is one of the most abundant natural antibodies in humans, constituting ~1% of immunoglobulins [ 26 , 27 , 28 , 29 , 30 ]. It is produced throughout life, starting few months after birth [ 26 , 31 ], in response to antigenic stimulation by gastrointestinal bacteria [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Anti-gal and The α-Gal Nanoparticlesmentioning
confidence: 99%